2018
DOI: 10.1155/2018/7372636
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into the Roles of MiRNAs in Metabolic Syndrome

Abstract: Metabolic syndrome (MetS), which includes several clinical components such as abdominal obesity, insulin resistance (IR), dyslipidemia, microalbuminuria, hypertension, proinflammatory state, and oxidative stress (OS), has become a global epidemic health issue contributing to a high risk of type 2 diabetes mellitus (T2DM). In recent years, microRNAs (miRNAs), used as noninvasive biomarkers for diagnosis and therapy, have aroused global interest in complex processes in health and diseases, including MetS and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 133 publications
1
35
0
Order By: Relevance
“…In our study, we observed obvious obesity and lipid deposition in liver of db/db mice consistent with the result of published studies [16,17]. MicroRNAs play an important role in a variety of diseases [18][19][20] including the lipid metabolic disorder [21,22], because they can regulate a wide range of growth and development processes [7]. Recent studies indicate that miR-27a [23], miR-194 [24] and miR-146b [25] can target different genes to regulate the development of NAFLD.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we observed obvious obesity and lipid deposition in liver of db/db mice consistent with the result of published studies [16,17]. MicroRNAs play an important role in a variety of diseases [18][19][20] including the lipid metabolic disorder [21,22], because they can regulate a wide range of growth and development processes [7]. Recent studies indicate that miR-27a [23], miR-194 [24] and miR-146b [25] can target different genes to regulate the development of NAFLD.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies suggest that adipose tissue can regulate liver metabolism by secreting various adipokines, including miRNAs [13]. miRNAs could negatively regulate the transcription of target genes [38], which were shown that played an important role in metabolic syndrome, especially related to the liver [39]. Studies had shown that specific miRNA expression profile was closely related to NAFLD [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have strongly implicated the microRNA system in regulating adipose tissue size and function [14][15][16]. For example, conditional deletion of Dicer from adipocytes inhibits lipogenesis in white adipocytes and produces severe depletion of white adipose tissue [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…Mice homozygous for the Tsnax (E126A) mutation display a metabolic profile that closely mimics that of Tsn KO mice.Selective deletion of Tsn or Tsnax from either adipocytes or hepatocytes, two candidate cell types, does not phenocopy the elevated adiposity displayed by mice with constitutive Tsn deletion or the Tsnax(E126A) mutation. Furthermore, global, conditional deletion of Tsn in adulthood does not elicit increased adiposity.Conclusion: Taken together, these findings indicate that inactivation of the TN/TX microRNA-degrading enzyme during development is necessary to drive the robust adiposity displayed by Tsn KO mice.Recent studies have strongly implicated the microRNA system in regulating adipose tissue size and function [14][15][16]. For example, conditional deletion of Dicer from adipocytes inhibits lipogenesis in white adipocytes and produces severe depletion of white adipose tissue [17,18].…”
mentioning
confidence: 99%